Mismatches: Os sertões, by Euclides da Cunha (1902), and the 2003 National Policy of Regional Development (PNDR) - Pinheiro, Robinson Santos (Geografares, 2020)
The objective is to inquire to what extent the imaginary about the Brazilian State presented in the novel Os Sertões, by Euclides da Cunha, may contribute to the interpretation of the spatial discourse presented in the National Policy of Regional Development - PNDR (Portuguese initials). To this end, an analysis of the aforementioned novel and the PNDR document was carried out through a bibliographic review. By reading Euclide’s text, it “aimed” the discussion about the role of the Brazilian state in relation to two central points: the integration of the national territory and the modernization of customs as in productive logics. The result of the mismatches is that Euclides thinking of integrating modernization of the Brazilian territory in “Os Sertões”, as long as the historical singularities are respected, remains current in the PNDR document.